STRUKTUR KEPEMILIKAN MANAJERIAL TERHADAP KEPUTUSAN INVESTASI DAN NILAI PERUSAHAAN - Misrah Misrah (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
This study aims to synthesize and test empirically the effect of ownership structure on firm value and investment decisions as intervening variables. The population of this study were manufacturing companies listed on the Indonesia Stock Exchange with an observation period from 2016 to 2022. The data collection method used was purposive sampling and a sample of 122 companies was obtained. then testing of all hypotheses in this study is to use path analysis through the Amos 20.0 program package. The findings of this study indicate that the ownership structure can reduce the tendency of managers to behave opportunistically. The increase in ownership structure affects the increase in firm value. The findings of this study indicate that ownership structure influences investment decisions. Finally, the findings of this study show that investment decisions are a variable mediating the causal relationship between ownership structure and firm value.